Fluoride stimulates the MAPK pathway to regulate endoplasmic reticulum stress and heat shock proteins to induce duodenal toxicity in chickens - Yanan Li; Tianwen Ma; Xiaoping Lv; Zongsheng Qiu; Shuxin Li; Jingjing Qi; Chengwei Wei (Poultry Science)
ABSTRACT: Fluoride is one of the essential trace elements for body. However, excessive fluoride poses a major threat to human and animal health. Fluorosis may cause pathological damage of the duodenum, but the underlying mechanism needs to be further studied. This study was to investigate the effects of long-term exposure to sodium fluoride (0, 500, 1,000, 2,000 mg/kg) on the duodenum of chickens. The results showed that after NaF exposure, intestinal epithelial cells were disarranged, necrotic or even exfoliated, goblet cells and mucus secretion were increased, and inflammatory response was induced in duodenal tissue. Oxidative stress, endoplasmic reticulum stress (ERs), and heat shock proteins (HSPs) are an adaptive response, however long-term, excessive changes are detrimental. Fluorosis activates ERs through IRE1, PERK and ATF6 pathways, increases the expression of HSP60, HSP70 and HSP90, and causes apoptosis and oxidative damage in duodenal tissue. In addition, fluorosis can activate the MAPK signaling pathway. This article can provide a reference for exploring the potential duodenal toxicity of sodium fluoride.